Komunikasi Pemasaran Transportasi Online NGuberJEK - Apsari Wahyu Kurnianti (Universitas Tidar, 2017)
Online transportation application is the solution for public transportation in Indonesia. It also created opportunites for various start up companies in Indonesia. NguberJEK created by PT UberJEK is one of the examples. PT NguberJEK focuses its marketing by reaching out to the municipalities in Java. However, business competition is now beginning to be seen in the municipalities of Magelang. It causes by the presence of larger online transport applications such as Gojek and Grab that are beginning to reach small towns across Java. To survive the competition, PT NguberJEK requires a mix strategy marketing with a focus on promotional components. PT NguberJEK's promotion strategy is expected to attract market attention.